1998
DOI: 10.1002/(sici)1096-9861(19981221)402:3<327::aid-cne4>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Superior area 6 afferents from the superior parietal lobule in the macaque monkey

Abstract: Superior area 6 of the macaque monkey frontal cortex is formed by two cytoarchitectonic areas: F2 and F7. In the present experiment, we studied the input from the superior parietal lobule (SPL) to these areas by injecting retrograde neural tracers into restricted parts of F2 and F7. Additional injections of retrograde tracers were made into the spinal cord to define the origin of corticospinal projections from the SPL. The results are as follows: 1) The part of F2 located around the superior precentral dimple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
135
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(156 citation statements)
references
References 7 publications
20
135
1
Order By: Relevance
“…Wise et al (1997) suggested that a synthesis of somatosensory, retinal, and extraretinal information occurs in MIP. Although this study could not differentiate independent connections, Matelli et al (1998) have suggested that area PEc (MDP) in the dorsomedial shoulder of the SPL (dorsal to area 7m) is most probably a higher‐order somatosensory area.…”
Section: Discussionmentioning
confidence: 64%
“…Wise et al (1997) suggested that a synthesis of somatosensory, retinal, and extraretinal information occurs in MIP. Although this study could not differentiate independent connections, Matelli et al (1998) have suggested that area PEc (MDP) in the dorsomedial shoulder of the SPL (dorsal to area 7m) is most probably a higher‐order somatosensory area.…”
Section: Discussionmentioning
confidence: 64%
“…Reports in other species of primate have indicated that posterior parietal connections of M1 focus on the rostral portions of this region (area 5), which are primarily related to processing of somatosensory inputs (e.g., Leichnetz,1986; Darian‐Smith et al,1993; Fang et al,2005). In contrast, tracer injections in the premotor areas often demonstrate additional connections with caudal regions of the parietal cortex, including high‐order stations of the visual “dorsal stream” (e.g., Matelli et al,1998; Marconi et al,2001; Tanné‐GariĂ©py et al,2002; Rozzi et al,2006). Thus, in order to help determine the rostral border of M1, we considered the pattern of projections between frontal fields and the posterior parietal cortex…”
Section: Resultsmentioning
confidence: 99%
“…With respect to parietal lobe connectivity, a number of investigators have shown that the medial preoccipital region is connected with the cortex of the intraparietal sulcus (areas LIP or POa, MIP, and VIP) and with areas 7m, 7a, and PEa (e.g., Seltzer and Pandya, 1980; Colby and Duhamel, 1991; Bullier et al, 1996; Shipp et al, 1998; Caminiti et al, 1999; Galletti et al, 2001). Finally, it has been shown that the medial preoccipital region is connected with the caudodorsal prefrontal and the dorsal premotor cortices (e.g., Barbas and Mesulam, 1981; Schall et al, 1995; Stanton et al, 1995; TannĂ© et al, 1995; Bullier et al, 1996; Matelli et al, 1998; Shipp et al, 1998; Caminiti et al, 1999; Petrides and Pandya, 2006).…”
Section: Discussionmentioning
confidence: 99%